Patient safety now : applying concepts, theories, and ideas for creating a safe environment - Woodward, Suzette (New York : Routledge, 2023)
Over the past decade or so, we have seen a multitude of improvement programmes and projects to improve the safety of patient care in healthcare. However, the full potential of these efforts and especially those that seek to address an entire system has not yet been reached. The current pandemic has made this more evident than ever. We have tended to focus on problems in isolation, one harm at a time, and our efforts have been simplistic and myopic. If we are to save more lives and significantly reduce patient harm, we need to adopt a holistic, systematic approach that extends across cultural, technological, and procedural boundaries. Patient Safety Now is about the fact that it is time to care for everyone impacted by patient safety, how we need to take the time to care for everyone in a meaningful way and how hospitals need to enable staff time to care safely. This book builds on the author's two previous books on patient safety. Rethinking Patient Safety talked about ways in which we need to rethink patient safety in healthcare and describes what we've learned over the last two decades. Implementing Patient Safety talked about what we can do differently and how we can use those lessons learned to improve the way we implement patient safety initiatives and encourage a culture of safety across a healthcare system. Patient Safety Now unites the concepts, theories and ideas of the previous two books with updated material and examples, including what has been learned by patient safety specialists during a pandemic. Patient Safety Now provides the reader with a unique view of patient safety that looks beyond the traditional negative and retrospective approach to one that is proactive and recognizes the impact of conditions, behaviours and cultures that exist in healthcare on everyone. It is written not only for healthcare professionals and patient safety personnel, but for patients and their families who all want the same thing. Too often when things go wrong, relationships quickly become adversarial when in fact this can be avoided by recognizing that, rather than being in separate camps, there are shared needs and goals in relations to patient safety.
DedicationAcknowledgementsAbout the AuthorIntroductionPart 1: How Did We Get Here?What is Safety-I?Policies and ProceduresWork as Done VersusWorkaroundOur Attitude to ErrorIt was 1980 SomethingPersonalizationExpertiseTeamsClinical Risk and RegulationThere is a Science to This!The 10%An Organization with a MemoryIncident ReportingIncident Analysis and InvestigationGlobal ChallengesAll ChangeSign Up to SafetyStill Not SafePart 2: Where Do We Want to Be?What is Safety-II?Risk ResilienceHuman FactorsComplex Adaptive SystemsPart 3: How Do We Get There?Safety-I and Safety-IIStudy the Mundane, the OrdinaryLearning From ExcellenceMind Your LanguageUnderstanding the Impact of IncivilityThinking About CultureInvestigating DifferentlyMoving Towards a Restorative Just CultureLearning about a Psychologically Safe EnvironmentImplementing the 4 Stages of Psychological SafetyImproving How We Talk to Each OtherDrawing Lessons from Change ManagementCaring For the People that CareLearning from COVID-19ConclusionReferences
"A Productivity Press book."
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Leadership; MEDICAL / Health Care Delivery; Medical errors -- Prevention; Patients -- Safety measures; Medical care -- Quality control; Medical care -- Safety measures; Corporate culture